2013
DOI: 10.1179/1743967113z.00000000066
|View full text |Cite
|
Sign up to set email alerts
|

Autoclave pyrolysis of carbon reinforced composite plastic waste for carbon fibre and chemicals recovery

Abstract: Carbon reinforced composite plastic (CRCP) waste has been pyrolyzed under nitrogen atmosphere in a batch stainless steel autoclave between temperatures of 350°C and 500°C and reaction times of up to 60 minutes. The reaction products were dominated by solid residue (72 -77 wt%), gas (2 -4 wt%) and liquid (22 -25 wt%). The solid residue consisted mainly of carbon fibre, giving up to 98 wt% recovery. However, the mechanical properties of the recovered fibres were lower when compared with a sample of virgin carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This process is limited to GF as no suitable study was found concerning CF. [65] further developed the process and successfully recycled CFRP waste-in which 98 wt% of the solid products (rCF) were recovered efficiently. The study stated that a reaction time increase could cause a decrease in the mechanical properties of the recycled CF.…”
Section: Vacuum Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…This process is limited to GF as no suitable study was found concerning CF. [65] further developed the process and successfully recycled CFRP waste-in which 98 wt% of the solid products (rCF) were recovered efficiently. The study stated that a reaction time increase could cause a decrease in the mechanical properties of the recycled CF.…”
Section: Vacuum Atmospherementioning
confidence: 99%
“…The study found that chemical modification on the surface of recycled CF and GF could improve fibre properties. Additionally, both studies [61,65] used secondary combustion (SC) to oxidise minor resin impurities and char formation on the pyrolysed fibres. When comparing the results, oxidised fibres retained the most mechanical properties when compared to non-oxidised fibres.…”
Section: Nitrogen Atmospherementioning
confidence: 99%
“…Pyrolysis process of CF/PBZ composites was also investigated for CF and chemical recovery . The pyrolysis gases were mainly CO 2 , CO, CH 4 , H 2 , and small amounts of other hydrocarbons with high caloric values.…”
Section: Polybenzoxazine/carbon Materials Compositesmentioning
confidence: 99%
“…Pyrolysis process of CF/PBZ composites was also investigated for CF and chemical recovery. [70,71] The pyrolysis gases were mainly CO 2 , CO, CH 4 , H 2 , and small amounts of other hydrocarbons with high caloric values. A maximum surface area of 802 m 2 g −1 was observed for the activated CFs after heating process at 850 °C for 5 h. Nitrogen adsorptiondesorption isotherms revealed that the resultant activated CFs were mostly microporous.…”
Section: Polybenzoxazine/carbon Fibers Compositesmentioning
confidence: 99%
“…However, the resulting fiber often has inferior mechanical properties to virgin material and becomes very difficult to disperse into second-generation products. In addition, the amount of energy and chemicals required to obtain these products is considerable [9][10].…”
Section: Introductionmentioning
confidence: 99%